Pengaruh Kelengkapan Sumber Belajar Terhadap Minat Belajar Siswa SMP Negeri 1 Dedai - Munawar Thoharudin; Yohanes Doni; Avelius Dominggus Sore (Universitas Negeri Padang, 2020)
The purpose of this study was to determine the completeness of student learning resources, student learning interest and to determine the effect of completeness of learning resources on student learning interest in Integrated social science subjects in sekolah Menengah Pertama Negeri 1 Dedai School year 2019/2020. The population in this study were all students sekolah Menengah Pertama Negeri 1 Dedai School year 2019/2020 as many as 168 students. This research method reveals quantitative by using the form of research that is the explanation format. This research data collection technique is indirect communication techniques and documentation. used were Likert scale questionnaire. research result There is a significant influence of the completeness of learning resources on student learning requests in integrated social science subjects as evidenced by the t value of 6.815 <t table 1.981. It can be concluded that the independent variable (X) tested has an influence on the dependent variable (Y). With the meaning of the word Ho is rejected and Ha is accepted.